(untitled) (AmeriQuests, 2021)
This paper analyzes exemplary art projects including and about refugees, projects committed to both, the arts scene and the community they want to serve. Considering the dilemmas of participation, we develop a conceptual framework: In that, we focus on the "figure of the third", playing a split and ambiguous role within the production as well as in the representation of these performances. Using the concept, we try to explain irony and cynicism as rhetorical effects and solidarity and paternalism as political effects. The framework is applied to investigate different stagings of (1) Charges: (The Supplicants) by Elfriede Jelinek and (2) Homohalal by Ibrahim Amir. In these stagings, participation proved to be overburdened with promises, but also allowed for diverse and partly unexpected results.